The Relationship of Music and Society: : Concept to Study, Influence of Social Structure and Social Change - Masiri, Phiphatphong (Connexion: Journal of Humanities and Social Sciences, 2024)
The purpose for writing this article is to explain that “How does music relate to society” the results of the study can conclusion in 3 points: (1) The relationship of music and society. It is something that arises from the need for communication and building relationships among people in society. Social connections can occur in many ways. So, music is involved in creating those social relationships. (2) The influence of social structure. The fact that music is brought into being a part of society. So, music can therefore reflect the structure of society. The influence of social structure has also caused changes in music as well. (3) The power to change of society. The way that music reflects the structure of society, music therefore has social power as if it were the structure of that society. The social power that arises with music. It has been used to change society that is facing various problems in order to create a greater understanding of the relationship between music and society. The author gives examples of musical phenomena occurring in different regions in this explanation by inserting those phenomena into the contents of various parts of this article.